2023
DOI: 10.1136/bmjopen-2021-056560
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of warm-up interventions on work-related musculoskeletal disorders, physical and psychosocial functions among workers: a systematic review

Abstract: ObjectivesThe aim of this systematic review was to identify from published literature the available evidence regarding the effects of warm-up intervention implemented in the workplace on work -related musculoskeletal disorders (WMSDs) and physical and psychosocial functions.DesignSystematic review.Data sourcesThe following four electronic databases were searched (from inception onwards to October 2022): Cochrane Central Register of Controlled Trials (CENTRAL), PubMed (Medline), Web of Science and Physiotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 111 publications
1
5
0
Order By: Relevance
“…In the topic of musculoskeletal disorders related to work, some obstacles are related to the work itself and the employer, and others, such as how to sit and stand up correctly, how to move the patient, and how to move the wheelchair, are related to the nurse, which can be led by teaching these things to promote self-efficacy in them. This finding is consistent with the results of van de Wijdeven’s ( 4 ) and Larinier et al’s studies ( 35 ). Training based on the PRECEDE-PROCEED model led to self-efficacy evaluation in nurses, and finally, the intervention improved self-efficacy.…”
Section: Discussionsupporting
confidence: 93%
“…In the topic of musculoskeletal disorders related to work, some obstacles are related to the work itself and the employer, and others, such as how to sit and stand up correctly, how to move the patient, and how to move the wheelchair, are related to the nurse, which can be led by teaching these things to promote self-efficacy in them. This finding is consistent with the results of van de Wijdeven’s ( 4 ) and Larinier et al’s studies ( 35 ). Training based on the PRECEDE-PROCEED model led to self-efficacy evaluation in nurses, and finally, the intervention improved self-efficacy.…”
Section: Discussionsupporting
confidence: 93%
“…Six reviews pursued the objective of identifying solely the effectiveness of PA interventions on promoting PA and/or reducing sedentary behavior (39, 41-43, 45, 54). Two reviews focused on the effects of PA interventions on improving psychological well-being and mental health (37,38,50,52) and two assessed workability (46,53). One review each showed a fitness approach (40,49) or focused musculoskeletal pain (48).…”
Section: Main Objectives Of the Reviewsmentioning
confidence: 99%
“…One review each showed a fitness approach (40,49) or focused musculoskeletal pain (48). Five reviews showed a combined approach regarding the objectives, considering physical activity behavior and health outcomes (38,40,44,47,52). The outcomes of the respective primary studies could be assigned to the following categories: physical activity-related outcomes (38, 39, 41-45, 47, 52, 54), health-related outcomes (37,38,40,44,(47)(48)(49)(50)52), and job-related outcomes (38,41,46,48,52,53).…”
Section: Main Objectives Of the Reviewsmentioning
confidence: 99%
See 2 more Smart Citations